2021
DOI: 10.1037/lhb0000440
|View full text |Cite
|
Sign up to set email alerts
|

Preventing school-based arrest and recidivism through prearrest diversion: Outcomes of the Philadelphia police school diversion program.

Abstract: Objectives: Created to combat the school-to-prison pipeline, the Philadelphia Police School Diversion Program offers voluntary community-based services to eligible youth accused of minor school-based offeses in lieu of arrest. This study evaluated program effectiveness in accomplishing goals related to reductions in school-based arrests, serious behavioral incidents, and recidivism. Hypotheses: We expected the annual number of school-based arrests in Philadelphia schools to decrease over the program's first 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…Finally, a quasi-experimental study sought to evaluate Philadelphia's effort to decrease the number of school-based arrested youth. Although the rate of school-based arrest decreased by 84 percent following the program's implementation, youth who were arrested prior to the program had similar recidivism rates compared with the program youth who, instead of being arrested at school, had a social worker visit their home and offer voluntary resources (Goldstein et al, 2021).…”
Section: Other Diversion Interventions and Practicesmentioning
confidence: 99%
“…Finally, a quasi-experimental study sought to evaluate Philadelphia's effort to decrease the number of school-based arrested youth. Although the rate of school-based arrest decreased by 84 percent following the program's implementation, youth who were arrested prior to the program had similar recidivism rates compared with the program youth who, instead of being arrested at school, had a social worker visit their home and offer voluntary resources (Goldstein et al, 2021).…”
Section: Other Diversion Interventions and Practicesmentioning
confidence: 99%
“…Fader et al (2015) evaluated a prearrest diversion program implemented in Utica, NY schools and identified a reduced number of school-based arrests in the 2 years after program implementation, though they did not see significant improvement in school-related outcomes among diverted students in that 2-year time frame. Additionally, short- and moderate-term outcome evaluations of a prearrest diversion program in Philadelphia—known as the Philadelphia Police School Diversion Program—indicated that the program was meeting its primary goal of reducing school-based arrests in the city without compromising school safety and produced promising findings related to reductions in number of diverted youths’ subsequent arrests and experiences of school discipline (Goldstein, Kreimer, et al, 2021; Goldstein, NeMoyer, et al, 2021).…”
Section: School-based Arrest As a Turning Pointmentioning
confidence: 99%
“…Additionally, given the chance that many young people experience their first contact with law enforcement while at school, targeting youth at risk for school-based arrest may further enhance the protective function of such diversion efforts. Perhaps as a result, jurisdictions across the country have begun implementing school-based diversion initiatives; however, only two such programs appear to have undergone empirical evaluation (Fader et al, 2015; Goldstein, Kreimer, et al, 2021; Goldstein, NeMoyer, et al, 2021).…”
Section: School-based Arrest As a Turning Pointmentioning
confidence: 99%
“…In a related effort, Philadelphia City's police department developed the Philadelphia Police School Diversion Program in collaboration with the City's school district, child‐care agencies, and the Department of Human Services to divert students, ages 10 and older without prior juvenile court adjudications, who commit misdemeanor offenses on school grounds to this diversion alternative. Results from the first five years of the project found an 84 percent decrease in school‐based arrests and a 34 percent decrease in serious behavioral incidents (Goldstein, Kreimer, Guo, Le, Cole, NeMoyer, Burke et al, 2021).…”
Section: The Challenge Of Srosmentioning
confidence: 99%